ENVIRONMENTAL QUALITY IN THE SEA WATERS OF KIEN GIANG - PHU QUOC - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2008)
Marine water quality in the seawaters of Kien Giang - Phu Quoc were relatively good. According to fishery standards, total suspended values (1.1 - 42.9 mg/1), DO (5.0 - 6.1 mg/1), BOD (0.9 - 1.9 mg/1) were usually within acceptable levels (TSS: 50 mg/1; DO: > 5 mg/1; BOD: 10 mg/l). Nutrient concentrations NH3,4-N (0 - 199.3 μg/l), NO2-N (0.1 - 100.9 μg/l), NO3-N (8.5 - 287 μg/l), PO4-P (2.9 - 27.7 μg/l) and hydrocarbon (308 - 633 μg/l) were sometime higher than the maximum standard (NH3,4-N: 70 μg/l; NO2-N: 55 μg/l; PO4-P: 15 μg/l; NO3-N: 100 μg/l and hydrocarbon: 300 μg/l), mainly in Rach Gia bay. Organic matters in sediment in the south of Phu Quoc island were moderate (organic C: 0.13 - 0.5%; organic N: 196-356 μg/l; total P: 100 - 268 μg/l). Organic matter deposited in the sediment traps were relatively high (organic C: 0.78 - 3.55%; organic N: 426 - 725; total P: 386 - 1778). Sedimentation rate was not high and ranged from 0.77 mg/cm2/day at Gam Gi island to 6.17 mg/cm2/day at Dam island. The impact of mainland on waters in the west and south of Phu Quoc island were unnoticeable. Therefore, environmental quality in this area mainly depended on natural conditions and socio-economic conditions in this island.